Stimulating Students’ Higher-Order Thinking Skills on Heat and Temperature Concepts - Indah Slamet Budiarti; Suparmi Suparmi; Sarwanto Sarwanto; Harjana Harjana; Viyanti Viyanti (Jurnal Pembelajaran Fisika, 2019)
The innovative way to improve the quality of human resources are elevated through education as one of basic foundation of human life. Education is a booster to form ideas, express thoughts, share feelings, and live a life as an individual. Education is also a significant factor that can change society and give new color to the community. This study aims to describe the process of stimulating students’ higher-order thinking skills on heat and temperature concepts. This research uses a descriptive method. Population in this study were high school students in Class XI in the city of Jayapura. The sampling technique in this study was purposive sampling so that a sample of 50 students was obtained. Research data collection using observation techniques and in-depth interviews. The results showed that students were able to build higher-order thinking skills by demonstrating cognitive activity focusing on the following processing classes: 63.7% of analysis skills, 23.9% of evaluation skills, and 12.4% of synthesis skills. These results represent that the activity of higher-order thinking skills stimulus process on heat and temperature concepts in learning. The process of this study could be functioned as an alternative strategy to encourage students to show the pattern of their higher-order thinking skills in the process of teaching and learning. This is the important findings in this study.Keywords: heat and temperature concepts, higher-order thinking skills, analysis skills, evaluation skills, synthesis skills, cognitive activity